Direct Extraction and Assessment of Genomic DNA of Mycetoma Fungi from Black-grains Specimen - Ahmed, Elhadi Abdalla; Nour, Bakri Y M; Abakar, Adam D; Ahmed, Gamal M. A.; Ahmed, Ahmed E (مجلة الجزيرة للعلوم الصحية; مجلد 17 عدد 1 (2021), 2022)
Background: Direct isolation of genomic DNA of mycetoma fungi from black-grains achieve rapid diagnosis and may overcome culture disadvantages. Objectives: This study aimed to isolate and assess the DNA of mycetoma fungi using black-grains and to apply amplification of ITS region and nucleotide sequences. Methods: CTAB method was followed by manual homogenization alternatively to liquid nitrogen and glass beads disruption to obtain the genomic DNA. Results: Yielded DNA concentrations vary from 1.50 to 47.97 μg/ml (mean 10.09 μg/ml) while the optimum DNA purity recorded with 75.8% of specimens (n=69/91).Successful amplification of ITS region was done using pan-fungal primers (ITS4/5) with 90.1 (n=82/91)percentage. Species nucleotide sequences were detected with 67 (94.4%) amplicons from a total of 71.Conclusion: The study recommended using of black-grain specimens for DNA extraction of mycetoma fungi parallel with culture to insure rabid diagnosis and identification.